Pro-Poor Growth Using Non-Income Indicators: An Empirical Illustration for Colombia - Adriana Cardozo; Melanie Grosse (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
In this paper, we analyze how the distribution of selected non-income welfare indicators changed between 1997 and 2003 in Colombia. We use multidimensional propoor growth measurement techniques and create indices for assets, health, education, and subjective welfare using two alternative weighing techniques: polychoric principal components and normatively selected weights. Results show that while income and expenditures fluctuated according to economic growth, reflecting the effects of the 1999 economic crisis, non-income indicators had minor changes. While income and expenditures decreased for all income percentiles, and relatively more for the richest, the non-income dimensions stagnated and remained in 2003 as unequally distributed as in 1997.
Keywords: D30; I30; O10; O12; 330; Pro-Poor Growth; Inequality; Welfare Measurement; Multidimensionality of Poverty; Latin America; Colombia